Viejos discursos, nuevos recursos. Los memes como herramienta de difusión de narrativas extremistas y de ultraderecha en el Perú - Trujillo Valverde, Said Ilich (2024)
This article aims to analyze one of the most prominent far-right collectives within the Peruvian digital space: Imperium.pe. Given that the presence and activities of this group are exclusively online, it is essential to examine not only the content of the speeches they promote, but also the predominant medium through which they are transmitted: internet memes, a digital format that has dominated online communication in recent years. By taking these memes as the starting point of our analysis, we can unveil the specific strategies that this collective employs to communicate its ideology, identify the target audiences for these speeches, and understand the reactions of the receivers. Additionally, it provides us with the opportunity to make a comparison between the resources employed and the themes addressed by Imperium and other similar politically leaning collectives in Latin America and worldwide. In this regard, our research will employ a combination of quantitative and qualitative methods. Thanks to exclusive access to Meta's official tool for searching, collecting, and analyzing the performance of publications, we will be able to compile all the relevant entries published by Imperium's Facebook page (its most active social platform) during the year 2023. The collected materials include text, images, and statistics on the generated reactions. In this way, we will form a corpus of memes that will be qualitatively analyzed with the aim of identifying the main themes addressed by this group and the resonance of each of them among the public. The analysis will be based on specialized literature on the phenomenon of the meme and the speeches it can convey, with special emphasis on the contributions of renowned researchers such as Limor Shifman or Bradley Wiggins. From the analysis, it is possible to verify a dangerous increase in the receptivity and dissemination of openly conservative, anti-feminist, and anti-multiculturalist speeches.